Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the quadratic equation [tex]\(x^2 + 2 = 20\)[/tex], follow these steps:
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 2 = 20 \][/tex]
Subtract 20 from both sides to get:
[tex]\[ x^2 + 2 - 20 = 0 \][/tex]
Simplifying this, we have:
[tex]\[ x^2 - 18 = 0 \][/tex]
2. Factor the quadratic expression:
Notice that the equation can be written as a difference of squares. The difference of squares formula is [tex]\(a^2 - b^2 = (a + b)(a - b)\)[/tex].
In this case, [tex]\(a = x\)[/tex] and [tex]\(b = \sqrt{18}\)[/tex] which simplifies to [tex]\(3\sqrt{2}\)[/tex]. Therefore:
[tex]\[ x^2 - (3\sqrt{2})^2 = 0 \implies (x - 3\sqrt{2})(x + 3\sqrt{2}) = 0 \][/tex]
3. Set each factor equal to zero:
Now, solve for [tex]\(x\)[/tex] by setting each factor equal to zero:
[tex]\[ x - 3\sqrt{2} = 0 \implies x = 3\sqrt{2} \][/tex]
[tex]\[ x + 3\sqrt{2} = 0 \implies x = -3\sqrt{2} \][/tex]
4. Write the solutions:
The solutions to the equation are:
[tex]\[ x = 3\sqrt{2} \][/tex]
[tex]\[ x = -3\sqrt{2} \][/tex]
Therefore, the solutions to the equation [tex]\(x^2 + 2 = 20\)[/tex] are [tex]\(x = 3\sqrt{2}\)[/tex] and [tex]\(x = -3\sqrt{2}\)[/tex].
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 2 = 20 \][/tex]
Subtract 20 from both sides to get:
[tex]\[ x^2 + 2 - 20 = 0 \][/tex]
Simplifying this, we have:
[tex]\[ x^2 - 18 = 0 \][/tex]
2. Factor the quadratic expression:
Notice that the equation can be written as a difference of squares. The difference of squares formula is [tex]\(a^2 - b^2 = (a + b)(a - b)\)[/tex].
In this case, [tex]\(a = x\)[/tex] and [tex]\(b = \sqrt{18}\)[/tex] which simplifies to [tex]\(3\sqrt{2}\)[/tex]. Therefore:
[tex]\[ x^2 - (3\sqrt{2})^2 = 0 \implies (x - 3\sqrt{2})(x + 3\sqrt{2}) = 0 \][/tex]
3. Set each factor equal to zero:
Now, solve for [tex]\(x\)[/tex] by setting each factor equal to zero:
[tex]\[ x - 3\sqrt{2} = 0 \implies x = 3\sqrt{2} \][/tex]
[tex]\[ x + 3\sqrt{2} = 0 \implies x = -3\sqrt{2} \][/tex]
4. Write the solutions:
The solutions to the equation are:
[tex]\[ x = 3\sqrt{2} \][/tex]
[tex]\[ x = -3\sqrt{2} \][/tex]
Therefore, the solutions to the equation [tex]\(x^2 + 2 = 20\)[/tex] are [tex]\(x = 3\sqrt{2}\)[/tex] and [tex]\(x = -3\sqrt{2}\)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.